The effect of age and chronic illness on life expectancy after a diagnosis of colorectal cancer: implications for screening. - Gross, Cary P; McAvay, Gail J; Krumholz, Harlan M; Paltiel, A David; Bhasin, Devina; Tinetti, Mary E (Annals of internal medicine, 2006)
Older adults with shorter life expectancies may receive less benefit from colorectal cancer screening than younger, healthier patients.
Keywords: Age Factors; Aged; Aged, 80 and over; Chronic Disease; Cohort Studies; Colorectal Neoplasms; Comorbidity; Cross-Sectional Studies; Female; Humans; Life Expectancy; Male; Mass Screening; Medicare; Retrospective Studies; SEER Program; Survival Rate